Two new records of Boesenbergia Kuntze (Zingiberaceae: Zingibereae) for the Flora of Myanmar - PIYAPORN SAENSOUK; SURAPON SAENSOUK; THAWATPHONG BOONMA; WIN PAING OO; NYI MIN HTET; CHARUN MAKNOI; BHANUBONG BONGCHEEWIN; NYI NYI HTWAY; HEIN MYAT MINN (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Saensouk P, Saensouk S, Boonma T, Oo WP, Htet NM, Maknoi C, Bongcheewin B, Htway NN, Minn HM. 2025. Two new records of Boesenbergia Kuntze (Zingiberaceae: Zingibereae) for the Flora of Myanmar. Biodiversitas 26: 480-489. This study reported two new records of Boesenbergia for Myanmar: Boesenbergia meghalayensis Aishwarya & M.Sabu, found in Yangon Region, and B. siphonantha (King ex Baker) M.Sabu, Prasanthk. & Škorni?k., found in Kayin State and Mon State. The study aimed to confirm the presence of these species in Myanmar through comprehensive taxonomic analysis based on morphological observations of living specimens collected from their natural habitats. Additionally, to expand the known distribution of Boesenbergia and support ongoing efforts to document the region's rich botanical diversity. Morphological characteristics were analyzed using specimens from natural habitats and compared with taxonomic literature and herbarium records. This study confirmed the presence of B. meghalayensis in Yangon Region and B. siphonantha in Kayin and Mon States as new records for Myanmar, along with verifying B. plicata in the Bago Region. These findings expand the distribution of Boesenbergia in Myanmar, providing an updated checklist and emphasizing the importance of taxonomic research for conservation and preserving the country’s plant diversity.